Assessment of biological indicators of specialized food product diabetic food "Inullact-Phyto" depending on the storage (Experimental biology, 2020)
In recent years, in a number of countries obtained as functional foods that improve a number of diseases are now widespread in modern people as atherosclerosis, obesity, osteoporosis, diabetes, as well as a new and promising direction of obtaining food products, improving public health and nutrition system with prebiotics enriched with microorganisms (bifido-lactobacilli), antioxidants, minerals, micro-elements, it shows the relevance of the work and compliance with the plan of action of the world health organization in the field of food and nutrition for 2015-2020.In this direction, within the framework of the grant funding of scientific projects of the Committee of science of the Ministry of education and science of the Republic of Kazakhstan for 2015-2017 for the purpose of a broad presentation of natural dairy bioproduct for the prevention and treatment of diabetes, the most common among modern diseases, a Specialized food product of diabetic nutrition "Inullact-Phyto" based on camel milk in combination with medicinal and natural food extracts creating normal conditions for the internal environment of the human body was developed and obtained.In assessing the quality of biological value of food products, as well as periods of storage of Specialized food diabetic food "Intellect-Phyto" is installed in full compliance, the indicators of biological activity and quality of security requirements TR CU 027/2012; TR CU 033/2013 app 4,8; TR CU 021/2011 Appendix 3; Standard of organization 9904400080043-01-2017; TR CU 022/2011 and contained the functional ingredients, the regulatory functions of the human body, and effective, the physiological level affects the shelf life to 60 days without stabilizers and preservatives.Key words: functional foods, camel milk, shubat, diabetes mellitus, Inullact-Phyto.